HUBUNGAN TINGKAT PENGETAHUAN KANKER PAYUDARA MAHASISWI AKPER DHARMA WACANA METRO TERHADAP PERILAKU MELAKUKAN SADARI - Immawati Immawati (AKPER Dharma Wacana, 2017)
Data about breast cancer in Indonesia continues to grow, even attack teenagers. Breast cancer is a malignancy that originates from cells in the breast. Breast cancer primarily affects women. Patients usually come in an advanced stage because of ignorance of breast cancer due to never check the condition of the breast regularly. Behavior of breast self-examination/BSE aims to prevent breast cancer as early detection. This study was to measure correlation between knowledge level of breast cancer student of Akper Dharma Wacana Metro and behavior of doing breast self-examination as early detection of breast cancer. Likert scale questionnaire analysis with cross sectional approach with chi square test. The subjects are level I, II and III student Akper Dharma Wacana Metro which amounted to 196 respondents, with each level I (68 respondents), level II (62 respondents), and level III (66 people). Result of research from 196 respondents on bivariate analysis got value p value more than alpha 0,05. Conclusion is no significant correlation between knowledge level of breast cancer student Akper Dharma Wacana Metro to behavior of breast self-examination as early detection of breast cancer